HUBUNGAN PENGETAHUAN IBU TENTANG MP-ASI DENGAN STATUS GIZI PADA BALITA - Herlina Agustiani (Nusantara Hasana Journal, 2023)
Child nutrition problems are broadly the impact of an imbalance between intake and output of nutrients (nutritional imbalance) which is influenced by patterns of complementary feeding (MP-ASI). The purpose of this research is to find out the relationship between mother's level of knowledge about MP-ASI. The research design used quantitative with the type of descriptive correlation design. The sample of this study were mothers of toddlers and toddlers 6-24 months as many as 35 respondents at Posyandu Mawar 2 Sangiang Jaya, Periuk District. The data analysis technique used was univariate analysis and bivariate analysis only. Based on the results of the study, the nutritional status of the toddlers was mostly normal, as many as 26 respondents (74.3%) at Posyandu Mawar 2 Sangiang Jaya, Tangerang City. There is no significant relationship between the level of mother's knowledge about MP-ASI and the nutritional status of toddlers aged 6-24 months.